Theology of Independence as a Foundation of Developing Catholic Education in Indonesian Context According to Y.B. Mangunwijaya - Carolus Borromeus Mulyatno (Journal of Asian Orientation in Theology, 2019)
Education is one of the forms of the Indonesian Church's apostolate. In the context of Indonesia that fought for its independence, Y.B. Mangunwijaya affirmed the importance of theology of independence as an anthropological foundation of developing a liberating education. By using analytical descriptive method, this research focuses on finding the main ideas of YB. Mangunwijaya about theology of independence as a foundation of education and learning process at school. There are three important things found in this research. First, theology of independence is the right formula that unites Christian values and the struggle for national life. It bases on the movement of Jesus Christ that is inclusive and universal for the sake of a more human life. Second, theology of independence becomes the foundation to develop a child-centered learning to develop or liberate themselves exploratively, creatively and integrally. Third, in order to develop liberating education, teachers who love children and dare to explore with the children for optimal child development are needed. Y.B. Mangunwijaya's thoughts provide a foundation for reconstructing the vision, mission and praxis of Catholic education in Indonesia contextually for a more liberating national life.